Mathematics education for girls in Prussia 1890–1925 - Krüger, Katja; Werth, Gerda (The Journal of Mathematical Behavior)

Checkliste zur Entwicklung und Implementierung einer hochschuldidaktischen Weiterbildung zur Förderung der bewegten Lehre - Waltert, Carolin (Gesundheitskompetenzen in Hochschulen entwickeln - Studierende für ihre berufliche Zukunft stärken)

Bewegte Lehre - Entwicklung und Implementierung einer hochschuldidaktischen Weiterbildung - Waltert, Carolin (Gesundheitskompetenzen in Hochschulen entwickeln - Studierende für ihre berufliche Zukunft stärken)

Studentische Gesundheitskompetenzen nachhaltig denken - Kehne, Miriam; Sting, Anna-Lena; Waltert, Carolin (Gesundheitskompetenzen in Hochschulen entwickeln - Studierende für ihre berufliche Zukunft stärken)

Unveiling the Distinctions: Computer Versus Sport-Specific Neurocognitive Tests - Gondwe, Benedict; Heuvelmans, Pieter; Benjaminse, Anne; Büchel, Daniel; Baumeister, Jochen; Gokeler, Alli (Journal of Sport Rehabilitation)
Context : Traditional assessments of high-order neurocognitive functions are conducted using pen and paper or computer-based tests; this neglects the complex motor actions athletes have to make in team ball sports. Previous research has not explored the combination of neurocognitive functions and motor demands through complex tasks for team ball sport athletes. The primary aim of the present study was to determine the construct validity of agility-based neurocognitive tests of working memory (WM) and inhibition. Methods : Twenty-seven athletes (5 females; mean age 24.2 [4.7] y; height 183.6 [9.1] cm; body mass 77.5 [11.2] kg) participated in the construct validity assessments that included computer-based tests (working memory capacity and stop-signal reaction time) and sport-specific assessments performed on the SpeedCourt system. Results : Construct validity analysis of sport-specific working memory yielded acceptable construct validity ( r = .465, P < .05), whereas the sport-specific stop-signal task resulted in low construct validity ( r = .179, P > .05). The poor construct validity results highlight the large variance between computer-based and sport-specific neurocognitive assessments. Conclusion : Sport-specific assessments are more complex and include more degrees of freedom potentially due to athletes’ center of mass displacement during task execution. These findings suggest that future research should focus more on the development of sport-specific assessments. These should include the cognitive and motor demands encountered during practice and competition, not use computer-based/pen and paper assessments for return to play decisions.

Precipitation Hardening in the Magnesium–Zinc–Calcium Alloy System - Braun, Marcel Patrick Klaus; Grydin, Olexandr; Hoyer, Kay-Peter; Schaper, Mirko (The Minerals, Metals & Materials Series)

Analyzing Symmetries of Swarms of Mobile Robots Using Equivariant Dynamical Systems - Gerlach, Raphael; von der Gracht, Sören (arXiv:2503.07576)
In this article, we investigate symmetry properties of distributed systems of mobile robots. We consider a swarm of n robots in the OBLOT model and analyze their collective Fsync dynamics using of equivariant dynamical systems theory. To this end, we show that the corresponding evolution function commutes with rotational and reflective transformations of R^2. These form a group that is isomorphic to O(2) x S_n, the product group of the orthogonal group and the permutation on n elements. The theory of equivariant dynamical systems is used to deduce a hierarchy along which symmetries of a robot swarm can potentially increase following an arbitrary protocol. By decoupling the Look phase from the Compute and Move phases in the mathematical description of an LCM cycle, this hierarchy can be characterized in terms of automorphisms of connectivity graphs. In particular, we find all possible types of symmetry increase, if the decoupled Compute and Move phase is invertible. Finally, we apply our results to protocols which induce state-dependent linear dynamics, where the reduced system consisting of only the Compute and Move phase is linear.
Keywords: dynamical systems; coupled systems; distributed computing; robot swarms; autonomous mobile robots; symmetry; equivariant dynamics

Using SysML as a Modelling Language for Dataspaces - Kulkarni, Pranav Jayant; Zerbin, Julian; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman (2024 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Utilizing data is crucial for economic success, but a lack of interoperability and concerns about the misuse of ones own data are hindering the cross-organizational use of data. Dataspaces provide the infrastructure necessary to integrate heterogeneous data sources within an organization or ecosystem, enabling seamless data interaction and interoperability. In addition, data spaces strengthen data sovereignty through their decentralized nature, which enables organizations to effectively control and manage their data. However, challenges persist in managing the complexity and dynamic nature of dataspaces, requiring significant resources and technical expertise. The decentralized nature leads to a large and diverse number of stakeholders, who need to agree on the use and scope of a dataspace. Modeling is a common approach to cope with technical complexity and heterogeneous stakeholders. In this paper, we propose a version of SysML and a corresponding method that focus on the modelling of data spaces. We provide a dataspace modelling method to unify the understanding of dataspaces and scope among all stakeholders to simplify the design and development process.

Musik und Arbeit
Der Band versammelt Beiträge zum vielgestaltigen Verhältnis von 'Musik' und 'Arbeit'. Zum einen wird Musik als Arbeit betrachtet, wobei Phänomene musikalischer Berufstätigkeit seit dem Mittelalter ebenso in den Blick geraten wie aktuelle Themen, etwa die Situation der Kreativwirtschaft im Kontext pandemischer Krisen. Zum anderen widmen sich die Fallstudien 'Arbeit' als Gegenstand oder Thema in Musik, so beispielsweise der musikalischen Nachahmung von Arbeitsprozessen und -geräuschen oder der musiktheatralen Darstellung der Arbeitswelt. Der Band versteht sich als eine Anregung für eine musikwissenschaftliche Auseinandersetzung mit dem Thema, aber auch für einen soziologischen Anschluss an musikbezogene Forschung.

Musik und Arbeit - Arbeit in der Musik. Einführende Überlegungen - Höink, Dominik; Feldhordt, Philip (Musik und Arbeit)

"Bergwerk muß blühen" - Arbeit als Oratoriensujet in der NS-Zeit - Höink, Dominik (Musik und Arbeit)

Einfluss von Schweißparametern und Montageverfahren auf die elektrische Kontaktgüte von Aluminium-Massebolzen - Haak, Viktor; Yang, Keke; Meschut, Gerson (Schweißen und Schneiden)
Ein wichtiger Bestandteil jeder Fahrzeugkarosserie sind Massebolzen, die zur Herstellung der elektrischen Schnittstelle zwischen der leitfähigen Karosserie und dem Bordnetz dienen. Eine zuverlässige Signal- und Leistungsübertragung erfor-dert minimale Übergangswiderstände an den elektrischen Anschlusspunkten des Massebolzensystems und muss ver-schiedenen Betriebs- und Umweltbedingungen über die gesamte Lebensdauer standhalten. Der Übergangswiderstand wird von mehreren Faktoren beeinflusst (z. B. Verbindungsgeometrie, Kontaktkraft, Temperatur, Werkstoff) und erhöht sich im Laufe der Betriebszeit infolge unterschiedlicher Alterungsmechanismen. Dieser Beitrag befasst sich mit der elektrischen Charakterisierung von Massebolzen aus AlMg5 mit einer ZnNi-beschichteten Stahl-Hutmutter auf einem AlMg3-Blech. Es werden ausgewählte fertigungs-, montage- und betriebsbedingte Einflussgrößen auf den elektrischen Verbindungs-widerstand analysiert. Als wirtschaftliche und etablierte Fügetechnologie kommt das Lichtbogenbolzenschweißen mit Hubzündung zum Einsatz. Zur Herstellung qualitativ hochwertiger Schweißverbindungen wird mittels einer statistischen Versuchsplanung ein geeigneter Referenzparametersatz ermittelt. Weiterhin wird der montagebedingte Einfluss anhand des Mutter-Anziehmoments bei der Kabelschuhmontage auf den elektrischen Verbindungswiderstand untersucht. Zusätzlich werden die Strombelastbarkeit und der maximal zulässige Betriebsbereich des Massebolzensystems ermittelt.

Umdenken! Vom fachlichen zum schulischen Experimentieren. Vorstellung einer Lehrkonzeption für angehende Physiklehrkräfte. - Webersen, Yvonne; Riese, Josef (HLZ – Herausforderung Lehrer*innenbildung)

From Knowledge To Intention: The Role Of TPACK And Self-Efficacy In Technology Integration - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Weiler, David (Computers and Education Open)

Vision: Towards True User-Centric Design for Digital Identity Wallets - Last, Yorick; Arias Cabarcos, Patricia (Symposium on Usable Security and Privacy (USEC) 2025)
To facilitate the growing demand for a universal means of digital identification across services, while preserving user control and privacy, multiple digital identity implementations have emerged. From a technical perspective, many of these rely on established concepts within cryptography, allowing them to provide benefits in terms of security and privacy. Recent legislation also promises broader recognition and acceptance of digital identities, both in the digital world and beyond. However, research into the usability, accessibility, and user understanding of digital identities is rare. We argue that the development of usable digital identity wallets is vital to the successful and inclusive application of digital identities in society. In this vision paper, we describe our research plans for obtaining a better understanding of how to develop these usable digital identities wallets.

Algorithm, expert, or both? Evaluating the role of feature selection methods on user preferences and reliance - Kornowicz, Jaroslaw; Thommes, Kirsten (Plos One)

Förderung von statistischem Denken im Mathematikunterricht der Primarstufe: Bedeutsame Ideen und Förderungsmöglichkeiten - Frischemeier, Daniel; Biehler, Rolf (Stochastik in der Schule)

Existierte Chremes? Vorüberlegungen zum Status der literarischen Fiktion bei Cicero - Siemoneit, Johannes Gabriel (Literarische Fiktionalität in der Vormoderne. Beiträge zu Problemen und Perspektiven)

Einleitung - Rühl, Meike; Siemoneit, Johannes Gabriel (Literarische Fiktionalität in der Vormoderne. Beiträge zu Problemen und Perspektiven)

Literarische Fiktionalität in der Vormoderne. Beiträge zu Problemen und Perspektiven